Identifying and Managing Frailty: A Survey of UK Healthcare Professionals - Frost, Rachael; Robinson, Katie; Gordon, Adam; Caldeira de Melo, Ruth; Villas Boas, Paulo J. F. [UNESP]; Azevedo, Paula S. [UNESP]; Hinsliff-Smith, Kathryn; Gavin, James P. (SAGE Publications, 2024)
Frailty is a common condition that leads to multiple adverse outcomes. Frailty should be identified and managed in a holistic, evidence-based and patient-centered way. We aimed to understand how UK healthcare professionals (HCPs) identify and manage frailty in comparison with UK Fit for Frailty guidelines, their frailty training, their confidence in providing support and organizational pathways for this. An online mixed-methods survey was distributed to UK HCPs supporting older people through professional bodies, special interest groups, key contacts, and social media. From 137 responses, HCPs valued frailty assessment but used a mixture of tools that varied by profession. HCPs felt confident managing frailty and referred older people to a wide range of supportive services, but acknowledged a lack of formalized training opportunities, systems, and pathways for frailty management. Clearer pathways, more training, and stronger interprofessional communication, appropriate to each setting, may further support HCPs in frailty management.
Keywords: ageing; frailty; geriatrics; healthcare; healthcare professionals; older people; online survey